Maharotul Qiraah Learning Method Based On Artificial Intelligence Word Wall - Bintang Rosada; Resdilla Pratiwi; Lia Agustina Damanik (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
Arabic reading (maharotul qira’ah) is an essential skill that often poses a challenge for learners, given the complexity of Arabic vocabulary, phonology, and grammatical structures. The urgency of mastering this skill is exacerbated by various internal and external barriers, such as pronunciation difficulties, lack of motivation, and limited environmental support. This study aims to evaluate the effectiveness of technology-based maharotul qira’ah learning methods, specifically the use of the artificial intelligence (AI)-powered Wordwall platform. Using a descriptive qualitative approach, data were collected through error analysis of midterm exam results and observed student performance development until the final semester exam. The results show that the use of Wordwall has a significant positive impact on reducing reading errors and improving student learning outcomes. This platform not only facilitates a more interactive and adaptive learning process but also overcomes various learning barriers. In conclusion, the integration of AI into Arabic reading learning methods can increase the efficiency and effectiveness of mastering maharotul qira’ah. This study recommends further development for widespread implementation in both formal and non-formal educational environments.